2023
DOI: 10.1063/5.0125969
|View full text |Cite
|
Sign up to set email alerts
|

A coupled awareness—epidemic model on a multi-layer time-varying network

Abstract: Social interactions have become more complicated and changeable under the influence of information technology revolution. We, thereby, propose a multi-layer activity-driven network with attractiveness considering the heterogeneity of activated individual edge numbers, which aims to explore the role of heterogeneous behaviors in the time-varying network. Specifically, three types of individual behaviors are introduced: (i) self-quarantine of infected individuals, (ii) safe social distancing between infected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In real life, once people realize the potential threat of disease, they will take effective measures to prevent infection in time, such as wearing masks, vaccination, etc. The awareness is reflected in the contact behavior that would change the connection patterns [24,25]. Therefore, scholars have begun to study the transmission dynamics of information and disease on multiple networks [26].…”
Section: Introductionmentioning
confidence: 99%
“…In real life, once people realize the potential threat of disease, they will take effective measures to prevent infection in time, such as wearing masks, vaccination, etc. The awareness is reflected in the contact behavior that would change the connection patterns [24,25]. Therefore, scholars have begun to study the transmission dynamics of information and disease on multiple networks [26].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, when disease outbreak occurs, disease-related information also diffuses among the population, and we learn about the risk of the disease and some preventive measures based on this information as a way to reduce our risk of being infected, which in turn has an important impact on the transmission of the disease [20][21][22][23][24][25]. Funk et al [22] analyzed the law of disease transmission based on the SIR model, and found that the diffusion of information can reduce the scale of the transmission of the disease; Granell et al [23] established UAU-SIS twolayer network model to study the coupled information and disease spreading law, and found that information can effectively inhibit disease transmission at the meta-critical point.…”
Section: Introductionmentioning
confidence: 99%